The Engineered Of Charcoal Briquette Cast Basic material From Tea Waste - Muhammad Fajar Arfani; Lukman Adlin Harahap; Adian Rindang (Jurnal Rekayasa Pangan dan Pertanian, 2016)
agricultural waste. One of  utilization of the agricultural waste is tea waste that into briquettes as an alternative energy to replace fuel oil and gas, as well as a raw material for the manufacture of activated charcoal. That is why the author made a cast to simplify charcoal briquette printing making process. This study used literature study, cast making, instruments testing and parameters observation. Parameters measured were was capacity, moisture content, ash content, heating value, economic analysis, break even point, net present value, and internal rate of return. The results showed the capacity was 2,907kg tool / h, average water content was 2,6%, average ash content was 6,357%, average calorific value was 5740,70 cal / g, cost was Rp. 25.750,46 for the first year, Rp. 25.453,35 for the second year, Rp. 25.354,45 for the third year, Rp. 25.305,08 for the fourth year, and Rp. 25.275,53 for the fifth year, the break even point 952,89 kg /year for the first year, 513,71 kg /year for the second year, 367,52 kg / year for the third year, 367,52 kg / year for the fourth year and 250,86 kg / year for the fifth year, net present value of Rp. 1.135.273.634,79, internal rate of return was 12,74%, its mean that this equipment was worthy to used. keywords: printing tools, charcoal briquettes, tea waste.